2006
DOI: 10.1164/rccm.200602-163oc
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Idiopathic Pulmonary Fibrosis

Abstract: Our results suggest that idiopathic pulmonary fibrosis is probably more common in the United States than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
844
2
42

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,155 publications
(910 citation statements)
references
References 35 publications
(31 reference statements)
22
844
2
42
Order By: Relevance
“…In this study, a statistically significant difference was seen with respect to the ages of the patients and the staining indices. The increase in number of myofibroblasts with age could be caused by fibrosis, which is a complication of tissue regeneration failure and ineffective epithelial repair, in organs which have an age dependant increase in mammalian tissue [18]. Louise et al, stated that fibrosis could be an adaptive response which was shown by mesenchymal cells, by secreting a provisional matrix to help in re-epithelialization, to restore tissue barrier function; but, a persistent, failed re-epithelialization and a persistent mesenchymal activation can result in a sustained and progressive fibrosis [19].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a statistically significant difference was seen with respect to the ages of the patients and the staining indices. The increase in number of myofibroblasts with age could be caused by fibrosis, which is a complication of tissue regeneration failure and ineffective epithelial repair, in organs which have an age dependant increase in mammalian tissue [18]. Louise et al, stated that fibrosis could be an adaptive response which was shown by mesenchymal cells, by secreting a provisional matrix to help in re-epithelialization, to restore tissue barrier function; but, a persistent, failed re-epithelialization and a persistent mesenchymal activation can result in a sustained and progressive fibrosis [19].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of case subjects were male and white (Table 1), reflecting the demographics of this disease (1,24). In general, affected individuals with telomerase mutations were similar to the familial and sporadic case subjects without telomerase mutations regarding smoking status, age at diagnosis, pathologic subtype of idiopathic interstitial pneumonia, and other comorbidities ( Table 2).…”
Section: Telomere Shortening In Pulmonary Fibrosis Subjects Without Mmentioning
confidence: 89%
“…The prototype of these diseases is idiopathic pulmonary fibrosis (IPF), the prevalence and annual incidence of which increase dramatically with age (1). A clue to the genetic underpinnings of the familial subtype of this disorder emerged from the discovery that a subset (z15%) of patients with IPF is heterozygous for mutations in the genes encoding the protein component (TERT) and the RNA component (TERC) of telomerase, a ribonucleoprotein enzyme that catalyzes the addition of hexameric nucleotide repeats to the ends of linear chromosomes (2,3).…”
mentioning
confidence: 99%
“…103 IPF affects approximately five million people worldwide, with 200,000 in the United States. 105 IPF is the most fatal of the interstitial lung diseases, with a median survival of <3 years. 106 The role of aging in IPF is incompletely understood.…”
Section: Fibrosis As a Disease Of Agingmentioning
confidence: 99%